Distal femur stress fracture: A unique case presentation in a youth rower - Altman, J. (Current Orthopaedic Practice, 2023)
Stress fractures are a relatively common and well documented injury among athletes and military recruites that typically result when repetitive mechanical stress on structurally normal bon exceeds intrinsic bone remodeling. This care report describes a rare presentation of a stress fracture of the distal femur in a competitive youth rower, in the absence of an obbious biomechanical mechanism given the lower impact nature of rowing, The injury was managed conservatively with rest, physical therapy, and gradual return to activity with the athlete making a full recovery. Prompt diagnosis and management ist important to prevent further complication and reduce return to play time in stress fractures. Informed written consent for publication of this case report was provided by the pathien and patient´s mother. Ethical approval was not required.